AWARENESS, IMPLEMENTATION, UTILIZATION ON THE HI- IMPACT 5 PROGRAM IN EASTERN VISAYAS, PHILIPPINES - Pearl Irish De Paz; Mae Geraldine E. Dacer; Sheilomay A. Majait; Jeruel A. Espinazo; Honey Rhoey B. Romero; John Anthony D. Romagos, (The Malaysian Journal of Nursing (MJN), 2022)
Background: One of the programs launched by the Department of Health (DOH) was the High Impact Five (HI-5) Program to intensify the implementation of the five major health programs namely infant care, childcare, maternal care, service delivery networks and HIV/ AIDS. Hence, it is important to assess the HI-5 program beneficiaries’ awareness, utilization and satisfaction as well as the program’s extent of implementation. Aim: The study aimed to determine the level of awareness, utilization, implementation, and satisfaction on the HI-5 Program in Eastern Visayas and to determine the relationship between variables. Methods: The study used descriptive correlation research design and survey questionnaires.Key informant interview and records review were used during the data collection process. Results: The study revealed that majority of the respondents were aware of the different HI-5 Program components with high to moderate utilization and satisfaction level on infant care, childcare, maternal care and service delivery networks components. However, the level of awareness, utilization and satisfaction levels were relatively low on the HIV/AIDS component. Likewise, there is a significant relationship found between the respondents’ level of awareness and utilization of the HI-5 program. Conclusion: The results of the study highlight the need to conduct further information dissemination campaign to increase the level of awareness, utilization, satisfaction and improve the extent of implementation on the HI- 5 Program among beneficiaries especially on the HIV / AIDS Component.